The Synthesis of Imidazoline Derivative Compounds as Corrosion Inhibitor towards Carbon Steel in 1% NaCl Solution - Deana Wahyuningrum; Sadijah Achmad; Yana Maolana Syah; Buchari Buchari; Bambang Ariwahjoedi (Institute for Research and Community Services (LPPM) ITB, 2008)
Oleic imidazoline is one of the nitrogen containing heterocyclic compounds that has been widely used as commercial corrosion inhibitor, especially in minimizing the carbon dioxide induced corrosion process in oilfield mining. In this present work, some imidazoline derivative compounds have been synthesized utilizing both conventional and microwave assisted organic synthesis (MAOS) methods, in order to determine their corrosion inhibition properties on carbon steel surface. The MAOS method is more effective in synthesizing these compounds than the conventional method regarding to the higher chemical yields of products (91% to 94%) and the shorter reaction times (7 to 10 minutes). The characterization of corrosion inhibition activities of the synthesized products towards carbon steel in 1% NaCl solution was determined by the Tafel plot method. The corrosion inhibition activities of compound 1b ((Z)-2-(2-(heptadec-8-enyl)-4,5-dihydroimidazol-1-yl)ethanamine), 2b ((Z)-2-(2-(heptadec-8-enyl)-4,5-dihydroimidazol-1-yl)ethanol) and 3b (2-(2-heptadecyl-4,5-dihydroimidazol-1-yl)ethanamine) at 8 ppm concentration in 1% NaCl solution are, respectively, 32.18%, 39.59% and 12.73%. The heptadec-8-enyl and hydroxyethyl substituents at C(2) and N(1) position of imidazoline ring, respectively, gave the most effective corrosion inhibition activity towards carbon steel compared to the presence of other substituents. The increase in concentrations of compound 1b, 2b and 3b in 1% NaCl solution tends to improve their corrosion inhibition activities. Based on the analysis of the free Gibbs adsorption energy (Ã„G0ads) values of compound 1b, 2b and 3b (-32.97, -34.34 and -31.27 kJ/mol, respectively), these compounds have the potential to interact with carbon steel through semi-physiosorption or semi-chemisorption.